Second relapse of solitary fibrous tumor within 20 years of initial resection. (May 2014) - Okabe, Ryo; Omasa, Mitsugu; Kurosawa, Manabu; Tokuno, Junko; Cho, Hiroyuki; Huang, Cheng-long
A 64-year-old woman presented with a sessile solitary fibrous tumor in the right thoracic cavity. She had undergone 2 solitary fibrous tumor resections 7 and 20 years previously. The latest histological findings were identical to the previous, and pathologically benign. However, we clinically classified the tumors as malignant because of repeated relapse. The tumor and extrapulmonary structures should be resected at the time of recurrence.